2002
DOI: 10.1002/1521-4095(20020418)14:8<605::aid-adma605>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Large Colloidal Crystals with Their (100) Planes Orientated Parallel to the Surfaces of Supporting Substrates

Abstract: Templating against two‐dimensional (2D) regular arrays of square pyramidal pits etched in Si(100) wafers has been exploited to fabricate colloidal crystals with their (100) planes oriented parallel to the substrates (see Figure for an SEM image). The capability and feasibility of this method have been demonstrated by crystallizing 1.0, 0.48, and 0.25 μm polystyrene beads into 3D opaline lattices having such an orientation over areas as large as several square centimeters. Like their (111)‐oriented cousins, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 11 publications
4
88
0
1
Order By: Relevance
“…11 Recently, Yin and co-workers have furthermore demonstrated the growth of fcc(100)-oriented colloidal crystals using an alternative templating procedure. 18 In their setup, 19,20 the patterned substrate is similarly oriented with respect to gravity as in our tilted horizontal setup.…”
mentioning
confidence: 99%
“…11 Recently, Yin and co-workers have furthermore demonstrated the growth of fcc(100)-oriented colloidal crystals using an alternative templating procedure. 18 In their setup, 19,20 the patterned substrate is similarly oriented with respect to gravity as in our tilted horizontal setup.…”
mentioning
confidence: 99%
“…Well -ordered high -quality lattices could not be observed using these methods. In order to confi ne and control colloidal assemblies, patterned topography of the substrate, like wells [83] , lithographically patterned reliefs [84] , or microfl uidic channels [85] are used in the literature. The ratio of the size of the particle to the size of the patterned feature affects the formation of the resulting lattices [86] .…”
Section: Templated Self -Assemblymentioning
confidence: 99%
“…The formation of specific microstructures within the colloidal crystals is important for the fabrication of opti- cal cavities, waveguides, and photonic chips. Besides control over the size, shape, and position of the aggregates, work demonstrated by Blaaderen, Ozin, and Xia et al showed that relief structure-assisted self-assembly can also provide effective control over the assembly structures [66,71,72]. For example, crystallization of colloidal particles on the substrates patterned with specific structures (e.g., square pyramidal pits) can produce face-centered cubic crystals with preferred orientations (see Fig.…”
Section: Templating With Relief Structuresmentioning
confidence: 99%
“…For example, crystallization of colloidal particles on the substrates patterned with specific structures (e.g., square pyramidal pits) can produce face-centered cubic crystals with preferred orientations (see Fig. 3.10) [66,71,72].…”
Section: Templating With Relief Structuresmentioning
confidence: 99%